Hematologic and serum biochemical reference intervals for wild eastern quolls (Dasyurus viverrinus): Variation by age, sex, and season. (25th February 2019) - Fancourt, Bronwyn A.; Nicol, Stewart C.
Abstract: Background: The eastern quoll ( Dasyurus viverrinus ) is an endangered carnivorous marsupial that has recently suffered significant population declines. Several small captive breeding populations have been established, with plans to translocate wild and captive individuals to areas of their former distribution. Accordingly, hematologic and serum biochemical reference intervals (RIs) established from wild eastern quoll populations are essential for monitoring the health and disease status of both captive and wild populations, and to evaluate the health of individuals before, during, and after translocation. Objectives: We aimed to establish hematologic and serum biochemical RIs for wild eastern quolls, and examine the effects of age, sex, and season. Methods: We collected a total of 202 hematologic samples, 309 packed cell volume samples, and 335 serum biochemical samples from 168 individual quolls between May 2011 and November 2013. Species‐level RIs were established, as well as RIs of groups separated by age (juvenile, adult) and sex (adult male, adult female) using nonparametric, robust, and parametric methods. Seasonal variation in age‐ and sex‐specific reference values was also assessed. Results: Strong age and seasonal variation were evident in many hematologic and serum biochemical analytes, with significant variation observed in serum biochemical analytes between the sexes. Conclusions: The observed age, sex, and seasonal variation reflect differences in the timing of growth and reproductive stressors, which interact with seasonal energetic demands. Our findings highlight the importance of using age‐, sex‐, and season‐specific RIs for clinical evaluation of eastern quolls, as species‐level RIs will inadvertently smooth and mask important seasonal fluctuations that reflect reproductive status at different times.